2001
DOI: 10.1099/0022-1317-82-2-283
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular evidence that Culex nigripalpus baculovirus is an unusual member of the family Baculoviridae

Abstract: We present evidence that a newly discovered mosquito virus from Culex nigripalpus is an unusual member of the family Baculoviridae. Development of this virus was restricted to nuclei of midgut epithelial cells in the gastric caeca and posterior stomach. The globular occlusion bodies were not enveloped, measured around 400 nm in diameter, occurred exclusively in nuclei of infected cells and typically contained four, sometimes up to eight, virions. The developmental sequence involved two virion phenotypes : an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 36 publications
4
71
0
3
Order By: Relevance
“…However, by 48 h p.i., most cells at the posterior midgut and gastric caeca were positive for viral gene expression and had swollen nuclei. 23 This indicates that the virus initially infects only a small group of cells but later spreads horizontally to infect other cells, presumably via budded virus. Interestingly, while most of the cells in the posterior midgut were positive for viral gene expression, none of the cells at the anterior midgut was positive for viral gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, by 48 h p.i., most cells at the posterior midgut and gastric caeca were positive for viral gene expression and had swollen nuclei. 23 This indicates that the virus initially infects only a small group of cells but later spreads horizontally to infect other cells, presumably via budded virus. Interestingly, while most of the cells in the posterior midgut were positive for viral gene expression, none of the cells at the anterior midgut was positive for viral gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Previous histological analysis has shown that many cells at the gastric caeca and posterior midgut of infected C. nigripalpus or C. quinquefasciatus larvae were heavily infected with CuniNPV occlusion bodies (OBs) and display signs of necrosis at the final stages of infection. 23,28 When TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) was applied to monitor possible apoptotic response to viral infection in C. quinquefasciatus larvae, there was no significant level of apoptosis at either early stage (2-8 h p.i.) or late stages (24 and 48 h p.i.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations